Review of The Gladiators vs. Spartacus: Dueling Productions in Blacklist Hollywood - Vernyik , Zénó (AMERICANA E-journal of American Studies in Hungary, 2022)
The Gladiators vs. Spartacus: Dueling Productions in Blacklist Hollywood Henry MacAdam, Duncan Cooper, and Fiona Radford Newcastle: Cambridge Scholars Publishing, 2020 2 vols. 486 + 621 pages ISBN 978-1-5275-5699-7 and 978-1-5275-6020-8 (hardcover) ISBN 978-1-5275-7153-2 and 978-1-5275-7154-9 (paperback)